The Effect Of Cooperative Integrated Reading And Composition (Circ) Technique On Reading Comprehension Of Narrative Text At Grade Eighth Students Of SMP Swasta GKPS 3 Pematang Siantar - Kesia Rahelin Simanjuntak; Dumaris E Silalahi; Yanti Kristina Sinaga (CV Putra Publisher, 2024)
This research aimed to find Out The Effect Of Cooperative Integrated Reading And Composition (Circ) Technique On Reading Comprehension Of Narrative Text At Grade Eighth Students Of Smp Swasta Gkps 3 Pematang Siantar. This research design is quantitative. The quantitative method is a planned and careful problems solving method. In quantitative, systematically control data collection design, and will focus on constructing inductively concluded theories within the framework of empirically proving hypothesis. The quantitative research imposes objective measuring to collect numeric data that are utilized the answers of questions or test the specified hypothesis. Researcher will choose two groups as the sample, namely class VIII.1 and VIII.2. The two classes that researcher will choose as sample have studied the narrative text based on school education curriculum. By calculating the data, we can conclude that the t-test result (2.42) exceeded the t-table value at a significance level of 0.05 (2.00), meaning 2.42 > 2.00. This indicates that the use of the CIRC technique has a significant impact on students' reading comprehension. This is evident from the list of student scores in reading comprehension when using the CIRC technique compared to the conventional technique. In other words, grade eighth students' capacity at SMP Swasta GKPS 3 Pematang Siantar in reading comprehension is significantly impacted by using of CIRC technique.